An Investigation into the linkage between Malaysian Listed Manufacturing Companies' Business Health and Financial Results - Pathak, Shaakalya; Liang, Foo See (Archives of Business Research, 2020)
Malaysia is widely considered to be a key leading economy in the Asia Pacific region. This research paper investigates the linkage between the business (or financial) health, as measured by the Altman Z-Score, and corporate performance, as measured by the Return on Equity (ROE), of listed manufacturing companies in this market (the ‘BURSA’ or Bursa Malaysia Stock Exchange, formerly known as the KLSE or Kuala Lumpur Stock Exchange). A linear regression has been conducted between these variables to determine the magnitude and direction of their relationships. The trends of Z-Scores over a five-year period have also been analysed. The analysis covers the period from 2013 to 2017 (inclusive) and yields a statistically positive correlation between ROE and the Z-Score for the market. Malaysia registered moderate-to-strong mean and median Z-Scores. These findings further support the strong economic position of this market as an Asian giant.